Induced desynaptic variation in poppy (Papaver somniferum L.) - Naseem,Sana (2013)
Cytological investigation of EMS (ethyl methane sulphonate) treated population demonstrated enhanced univalent frequency per cell with unequal separation at Anaphase I. In contrast to controlled plants, medium strong type desynaptic plants were obtained from 0.6 % EMS treated set, revealing high frequency of univalents at Metaphase I, along with bivalents, which were loosely paired. The univalents remained unpaired till the end of meiosis, leading to formation of micronuclei and abnormal tetrads. These plants had high pollen inviability and sterile seeds. It might be possible that EMS had acted on some genes responsible for chiasma formation, resulting in early chiasma dissociation, which suggests that EMS can act as a potential tool in the development of male sterile lines. The study demonstrated the feasibility of chemical mutagenesis in mutation breeding programme on poppy (Papaver somniferum L.).